k-Yamabe and quasi k-Yamabe solitons on imperfect fluid Generalized Robertson - Walker spacetime - Mohd Danish Siddiqi; Shah Alam Siddiqi (Mathematical Physics and Computer Modeling, 2022)
In this research article, we estimate the behavior of an imperfect fluid generalized Robertson - Walker spacetime (GRW) in terms of k-Yamabe soliton with torseforming vector field. Besides this, we evaluate a specific situation when the potential vector filed ξ is of the form of gradient i.e, ξ = grad(Ψ), we extract a Laplace-Poisson equation, and Liouville equation from the quasi k-Yamabe soliton equation.